Targeting sedentary behavior as a feasible health strategy during COVID-19. Issue 3 (29th October 2020) - Zieff, Gabriel; Bates, Lauren C; Kerr, Zachary Y; Moore, Justin B; Hanson, Erik D; Battaglini, Claudio; Stoner, Lee
Abstract: Sedentary behavior is associated with poor physical and mental health. Targeting sedentary behavior is a simple strategy that may help counter physical and mental health concerns associated with COVID-19-related social restrictions. Of course, traditional strategies such as achieving optimal exercise and physical activity levels are also important and should be recommended. However, even under normal circumstances, the difficulty in promoting lasting exercise habits at multiple levels (e.g. individual, environment, policy) are well documented, and chances of maintaining or improving these factors is now even lower. Thus, relative to other lifestyle behaviors – sedentary behavior may be more amenable to change. Moreover, reducing sedentary behavior may be less susceptible to influence from factors associated with health disparities such as age, race, and socio-economic status compared to exercise or physical activity. Sedentary behavior is a feasible health strategy that should be targeted during COVID-19. Abstract : Reducing sedentary behavior is a realistic strategy to help combat the negative physical and mental health consequences associated with the COVID-19 pandemic.